Thermogel Delivers Oxaliplatin and Alendronate in situ for Synergistic Osteosarcoma Therapy - Sun, Yifu; Li, Ke; Li, Chen; Zhang, Ying; Zhao, Duoyi (Frontiers in Bioengineering and Biotechnology, 2020)
The therapeutic effect of osteosarcoma (OS) has not made extraordinary progress in the past few decades. Oxaliplatin (OXA) is a widely used clinical anti-tumor drug. Recent studies have shown that OXA can trigger anti-tumor immunity by inducing immunogenic death (ICD). Alendronate (ALN) has been used to threaten the skeletal system tumors because of the unique bone affinity and the ability to inhibit bone destruction. In this study, we co-loaded OXA and ALN on mPEG45–PLV19 thermo-sensitive hydrogel to perform in situ treatment on the mouse OS model. Slowly released OXA can induce immunogenic death of tumor cells. At the same time, thermo-sensitive hydrogels can induce the accumulation of cytotoxic T lymphocytes. Besides, ALN could synergistically diminish tumors and prevent bone destruction. This system could synergistically inhibit the progression of OS and lung metastasis and has no toxicity to various organs throughout the body.